2000
DOI: 10.1016/s0895-7061(00)01201-2
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol inhibits cholinergic vasodilatation in the human forearm

Abstract: Exogenous cortisol raises blood pressure (BP) in humans and there is accumulating evidence of abnormalities of glucocorticoid activity in essential hypertension. In this study we tested the hypothesis that exogenous cortisol attenuates the cholinergic dilator response in the forearm circulation. Fourteen healthy normotensive men were studied. Using bilateral forearm venous plethysmography, we examined forearm blood flow responses to intra-arterial acetylcholine (ACh) and sodium nitroprusside (SNP) pre- and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 27 publications
7
66
4
Order By: Relevance
“…Cortisol did not affect the response to sodium nitroprusside, and although N G -monomethyl-L-arginine inhibited cholinergic vasodilation in placebo-treated subjects, it had no additional effect in the presence of cortisol. 6 Taken together, these results are consistent with a role for abnormalities of the nitric oxide system in cortisol-induced hypertension in humans.…”
supporting
confidence: 75%
“…Cortisol did not affect the response to sodium nitroprusside, and although N G -monomethyl-L-arginine inhibited cholinergic vasodilation in placebo-treated subjects, it had no additional effect in the presence of cortisol. 6 Taken together, these results are consistent with a role for abnormalities of the nitric oxide system in cortisol-induced hypertension in humans.…”
supporting
confidence: 75%
“…The results of our correlation analysis are in accordance with findings of Akaza et al [15] who showed a significant negative correlation between percentage changes in brachial artery diameter during flow mediated dilatation and morning cortisol levels in patients of CS. Although morning serum cortisol level is not considered to be a disease marker in CS due to its inherent inter-individual variations independent of the disease status, our findings indicate the probable pathophysiologic role excess cortisol levels can play in the causation of vascular endothelial dysfunction as already been shown by previous studies [9][10][11].…”
Section: Discussionsupporting
confidence: 55%
“…MP150 (BIOPAC Systems Inc., CA, USA), a computer based digital data acquisition system with Ethernet interfacing and software Acqknowledge® 3.8.2 was employed to record ECG and PPG signals at a sampling rate of 1kHz. PPG acquisition unit essentially comprised of an infrared (860±6 nm), reflection type photoelectric transducer (TSD200) and a biopotential amplifier (PPG100C) with a preset of gain and acetate [11], based on forearm blood flow responses to reactive hyperemia and intra-arterially infused acetylcholine respectively. In both these studies patients and subjects were shown to be free of any of the clinical or biochemical features of glucocorticoid induced metabolic syndrome suggesting that excess glucocorticoid levels can per se affect vascular endothelial function.…”
Section: Assessment Of Vascular Functionmentioning
confidence: 99%
“…Furthermore, it has been shown that glucocorticoids, more particularly cortisol, induce a downregulation of eNOS in endothelial cells as well as a decrease in plasma NOx levels (Wallerath et al, 1999;Rogers et al, 2002). Chronic cortisol administration to healthy human controls is also associated with decreased endothelium-dependent flow-mediated dilatation, which reflects endothelial NO production (Mangos et al, 2000). The HPA axis hyperactivity found in MD could therefore be responsible, at least partially, for the endothelial and platelet NO dysregulations observed in MD patients, which in turn could mediate some of the deleterious CV effects of HPA hyperactivity in MD patients.…”
Section: Discussionmentioning
confidence: 99%